Distribution and Succession Feature of Antibiotic Resistance Genes Along a Soil Development Chronosequence in Urumqi No.1 Glacier of China - Shen, Ju-Pei; Li, Zong-Ming; Hu, Hang-Wei; Zeng, Jun; Zhang, Li-Mei; Du, Shuai; He, Ji-Zheng (Frontiers in Microbiology, 2019)
Primary succession of plant and microbial communities in the glacier retreating foreland has been extensively studied, but shifts of antibiotic resistance genes (ARGs) with the glacier retreating due to global warming remain elusive. Unraveling the diversity and succession features of ARGs in pristine soil during glacier retreating could contribute to a mechanistic understanding of the evolution and development of soil resistome. In this study, we quantified the abundance and diversity of ARGs along a 50-year soil development chronosequence by using a high-throughput quantitative PCR (HT-qPCR) technique. A total of 24 ARGs and two mobile genetic elements (MGEs) were detected from all the glacier samples, and the numbers of detected ARGs showed a unimodal pattern with increasing trend at the early stage (0 ~ 8 years) while no significant change at later stages (17 ~ 50 years). The oprJ and mexF genes encoding resistance to multidrug were the only two ARGs that detected across all the succession ages, and the mexF gene showed an increasing trend along the succession time. Structural equation models indicated the predominant role of the intI1 gene encoding the Class 1 integron-integrase in shaping the variation of ARG profiles. These findings suggested the presence of ARGs in pristine soils devoid of anthropogenic impacts and horizontal gene transfer mediated by MGEs may contribute to the succession patterns of ARGs during the initial soil formation stage along the chronosequence.